DYNAMIC CALCULATION CORRECT N-COAL, TRIANGULAR AND RHOMBIC PLATES WITH HINGE A SUPPORT ON A CONTOUR WITH USE OF THE RELATIONS OF CONFORMAL RADIUSES AS GEOMETRICAL ARGUMENT - А Aleksandrovich Сhernyaev (Structural Mechanics of Engineering Constructions and Buildings, 2012)
For definition of the basic frequency natural vibration elastic isotropic of correct n-coal, triangular and rhombic plates with hinge a support on a contour is suggested to use the uniform for all settlement function of one variable. As this variable acts the new argument of geometrical methods of the decision of two-dimensional problems of building mechanics - dimensionless geometrical characteristic of the form of flat area - the relation internal to the external conformal radiuses